Length Matters: One Additional Methylene Group in a Reactant is Able to Affect the Reactivity Pattern and Significantly Increase the Product Yield; Synlett; Vol. 29, iss. 15 - Stepanova E. V. Elena Vladimirovna; Podvalniy N. M.; Abronina P. I. Polina Igorevna; Kononov L. O. Leonid Olegovich (2018, 2018)
Title screen